Theology and therapy: Maintaining the connection - Fergusson, David (Pacifica, 2013)
The important interaction of theology and psychotherapy in the mid-20th century is reviewed, with particular attention given to the formative role of personalist philosophy and its practical outcomes. After exploring the reasons for the relative decline in the interaction of these disciplines, at least as far as much mainstream theology is concerned, some proposals are offered for reinvigorating the links. These involve recognizing the therapeutic and liturgical significance of traditional theological themes such as self-love, providence and vocation.